Additions, corrections, and bibliographic issues on the Heteropteran fauna of Korea (Insecta: Hemiptera) - Kim, Wonwoong; Oh, Minsuk; Kim, Wongun; Ahn, Soojeong; Cho, Geonho (Zootaxa, 2025)
We address issues of faunistic studies on Korean true bugs (Hemiptera: Heteroptera) and critically review the literature records on recently (2011–2024) reported species. Furthermore, 18 species in 11 families are newly reported from Korea: Cimicomorpha—Anthocoridae: Elatophilus (Elatophilus) nipponensis Hiura, 1966, Temnostethus (Temnostethus) gracilis Horváth, 1907; Miridae: Stethoconus takaii Nakatani & Yasunaga, 2018, Yamatofulvius miyamotoi Yasunaga, 2000; Reduviidae: Oncocephalus heissi Ishikawa, Cai & Tomokuni, 2006, Polytoxus fuscovittatus (Stål, 1860); Tingidae: Physatocheila nigrintegerrima Souma, 2019; Pentatomomorpha—Aradidae: Aradus unicolor Kiritshenko, 1913, Aneurus (Aneurodes) taterasanus Shimamoto & Ishikawa, 2022, Neuroctenus quercicola Nagashima & Shono, 2003, Mezira pygmaea Hsiao, 1964; Cydnidae: Parachilocoris japonicus Lis, 1994; Lygaeidae: Arocatus rufipes Stål, 1872; Pachygronthidae: Pachygrontha similis Uhler, 1896; Pentatomidae: Niphe elongata (Dallas, 1851); Pyrrhocoridae: Dysdercus (Paradysdercus) evanescens Distant, 1902; Rhyparochromidae: Appolonius oblongus Tomokuni, 1995, Neolethaeus lewisi (Distant, 1883), of which five species are recorded based on photographic evidence. Eleven species are excluded from the Korean fauna based on review of literature records: Acanthosomatidae: Elasmucha signoreti Scott, 1874, Lindbergicoris gramineus (Distant, 1883); Aradidae: Brachyrhynchus taiwanicus (Kormilev, 1957), Daulocoris formosanus Kormilev, 1971, Mezira subtilis Josifov & Kerzhner, 1974; Miridae: Apolygus nigrovirens (Kerzhner, 1988), Neolygus lobatus (Linnavuori, 1963), Kasumiphylus ryukyuensis (Yasunaga, 1999), Tytthus parviceps (Reuter, 1890); Pentatomidae: Erthesina fullo (Thunberg, 1783), Plautia splendens Distant, 1900. Three species are reconfirmed from Korea: Geocoridae: Geocoris (Geocoris) proteus Distant, 1883; Rhyparochromidae: Caridops pseudadmistus Zheng, 1981; Veliidae: Halovelia septentrionalis Esaki, 1926.